1987
DOI: 10.1063/1.452130
|View full text |Cite
|
Sign up to set email alerts
|

Nonadditivity of a bi n i t i o pair potentials for molecular dynamics of multivalent transition metal ions in water

Abstract: A b initio molecular orbital pair potentials for the interaction of Fe2+ and Fe3+ ions with H2O are reported. Molecular dynamics calculations of the static structure of the solvation shell of Fe2+ and Fe3+ in water using the ab initio pair potentials gives physically incorrect results, i.e., the coordination numbers are eight instead of six as observed experimentally. This problem has also been encountered by other workers for divalent transition metal ions in water. By computing three-body energies from the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(129 citation statements)
references
References 28 publications
12
115
1
1
Order By: Relevance
“…The same reasoning can be applied to the decomposition in the case of the two-body approach, ⌺E 2-body , but it should be noted that water-water repulsions should be less affected by not including the ionic polarization, given that the considered structures only involved two water molecules. As already pointed out by Probst 62 and Curtiss et al, 13 it is observed that many-body contributions are more important in the hydrated ion-water interactions than in the water-water ones.…”
Section: ͑4͒supporting
confidence: 53%
See 2 more Smart Citations
“…The same reasoning can be applied to the decomposition in the case of the two-body approach, ⌺E 2-body , but it should be noted that water-water repulsions should be less affected by not including the ionic polarization, given that the considered structures only involved two water molecules. As already pointed out by Probst 62 and Curtiss et al, 13 it is observed that many-body contributions are more important in the hydrated ion-water interactions than in the water-water ones.…”
Section: ͑4͒supporting
confidence: 53%
“…69 In ionic aqueous solutions containing highly charged cations, the ion-solvent interactions are clearly dominant in a widespread region around the cation, determining a large part of the polarization effects on the water molecules. 13,39,62 Because the dipole moment of the MCHO model responds to polarization, we can look into the value of this magnitude at different distances from the hexahydrate ͑Table III͒. The dipole of the second-shell waters is much larger than the dipole of bulk waters, reflecting the strong ionic field to which the former molecules are subject.…”
Section: B Monte Carlo Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This overestimation has been previously reported in simulations of ionic solutions 37 and attributed to large many-body effects. 38 The peaks corresponding to the second hydration shell are centered at 4.26 Å ͑Q3S-O RDF͒, 4.02 Å ͑Q3B-O RDF͒, and 4.07 Å ͑HI-O RDF͒ and integrates to 18 ͑Q3S-O͒, 25 ͑Q3B-O͒, and 14 ͑HI-O͒ oxygen atoms. Cation-hydrogen RDF for the solution containing Q3S presents a wide peak corresponding to the second shell centered at 4.8 Å ͑the integration number is 44͒, the Q3B presents a wide double peak at 4-5 Å which integrates to ϳ55 hydrogen atoms, and the HI presents a wide peak centered at 4.65 Å ͑the integration number is ϳ32͒.…”
Section: A Structural Resultsmentioning
confidence: 99%
“…Water potentials were also tested on bulk ice. Fe-O parameters were obtained by fitting the water model (Rustad et al 1995) to the ab initio calculations of the iron-water potential surface of Curtiss et al (1987). Using the water-water from Halley et al (1993) and Fe3+-water potential model in Rustad et al ( 1995), the Fe-O distance in the hexaaquo complex is 207 pm.…”
Section: Molecular Simulation Of Oxidementioning
confidence: 99%